1D Radiative Fluid and Liquid Crystal Equations - Qin, Yuming (EDP Sciences, 2022)
This book presents recent results on nonlinear evolutionary fluid equations, in particular the global well-posedness and asymptotic behavior of solutions to 1D radiative fluid equations, as well as liquid crystal equations. Most of the material in this book was prepared by the author over the past few years.This book has two main features. Firstly, there are more known results on higher dimensional radiative fluid systems but only on the local existence and explosion of solutions; while the existing findings on the one-dimensional case present some shortcomings, this book introduces corrections and improvements of these shortcomings. Secondly, the current findings on the high-dimensional compressible liquid crystal fluid equations are few and include only globally existing solutions but not the asymptotic behavior of the solutions; the author developed not only the global existence and regularity of the solutions, but also the asymptotic behavior of the solutions for the one-dimensional case in the chapter 3 of this book. Therefore, this work provides the reader with complete elements related to the one-dimensional compressible liquid crystal fluid system